Corrigendum to “Influence of silica fume addition and content on the early hydration of calcium aluminate cement — The role of soluble silicon” [Cem. Concr. Res. 184 (2024) 107618] (Cement and Concrete Research (2024) 184, (S0008884624001996), (10.1016/j.cemconres.2024.107618)) - Schramm, Tillmann; Neubauer, Jürgen; Götz-Neunhoeffer, Friedlinde (Cement and Concrete Research, 2025)
The authors regret a calculation error regarding the dilution factor which affects the absolute ion concentration values stated in the above paper and therefore also the corresponding calculated saturation indices. All stated concentration values (text and figures) need to be multiplied by a factor of 2.25. However, the authors would like to highlight that this does not affect any statements or conclusions made throughout evaluation and discussion of the data since it was focused on the qualitative evolution and comparison of the mixes. All affected figures were updated and are provided below (Figs. 8–12), including the recalculated saturation indices with the corrected concentrations (Fig. 9). For any sections in the text, it is referred to the correction factor of 2.25. The authors would like to apologise for any inconvenience caused.[Figure presented][Figure presented][Figure presented][Figure presented][Figure presented]
CRIS-Team Scopus Importer:2025-01-31